PYROLYSIS OF MERANTI SAWDUST (Shorea spp) WITH Ni/SBA-15 CATALYST USING PYROLYSIS GAS CHROMATOGRAPHY MASS-SPECTROMETRY (Py-GC/MS) - Fitriah, Nur Azizah; Subagyono, R. R Dirgarini J.N.; Allo, Veliyana Londong (PROSIDING SEMINAR KIMIA, 2023)
Pyrolysis of meranti sawdust (Shorea spp) with Ni/SBA-15 catalyst at 350°C, 450°C and 550°C using the pyrolysis-Gas Chromatography-Mass Spectrometry (Py-GC/MS) technique was carried out. This research was conducted to determine the pyrolysis product and the chemical composition of the pyrolysis product of meranti sawdust catalyzed by Ni/SBA-15 (20%wt.%). Based on the area percentage of products identified on the pyrogram, the chemical compositions of the pyrolysis product of meranti wood were 32.4%-43.6% products derived from cellulose/hemicellulose and 32.7%-23.3% products derived from lignin. The addition of Ni/SBA-15 catalyst to the pyrolysis of meranti sawdust increased the formation of cellulose/hemicellulose derivative products such as furan and furfural, as well as lignin derivative products such as vanillin. However, increasing the concentration of the catalyst also improved the amount of acetic acid, which is potentially corrosive and detrimental. Keywords: Pyrolysis, Meranti sawdust, Catalyst Ni/SBA-15, Py-GC/MS